2006
DOI: 10.1002/app.25185
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical properties of poly(L‐lactic acid) nucleated by dibenzoylhydrazide compound

Abstract: Benzoylhydrazide compounds were evaluated as a nucleating agent for poly(L-lactic acid) (PLA). From the results of the differential scanning calorimetry, octamethylenedicarboxylic dibenzoylhydrazide (OMBH) was found to be most effective for acceleration of PLA crystallization under higher cooling rate of À508C min À1. PLA with OMBH of 1 wt % exhibited very short crystallization half-time with wide range of isothermal temperature from 90 to 1308C. The molding cycle time of PLA with OMBH in injection molding was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
93
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 11 publications
3
93
0
Order By: Relevance
“…In another study, a series of organic compounds having hydrazide end-groups were evaluated in terms of their nucleating abilities. Best results, obtained with benzoylhydrazide compounds, showed increased crystallization temperature upon cooling and led to fully crystallized samples at moderate cooling rates (À20 C/min) [19]. Unfortunately, these compounds are not readily available as they have only been synthesized at the laboratory scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, a series of organic compounds having hydrazide end-groups were evaluated in terms of their nucleating abilities. Best results, obtained with benzoylhydrazide compounds, showed increased crystallization temperature upon cooling and led to fully crystallized samples at moderate cooling rates (À20 C/min) [19]. Unfortunately, these compounds are not readily available as they have only been synthesized at the laboratory scale.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no systematic study on the effect of molding conditions on the crystalline development in PLA. Recently, however, it was shown that PLA nucleated with organic compounds (benzoylhydrazide compounds) could be molded into highly crystalline parts [30]. The increased heat distortion temperature, over 120 C, clearly exhibits the benefits of fully crystallized PLA.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [2] found that a reactive organoclay with glycidyl functionality acts as a compatibilizer for PLLA/PBS blends, improving the elongation at break and tensile modulus [4]. Homklin et al [8] clarified the effect of nucleating agents on the PLLA/PBS blend properties: adding nano-sized calcium carbonate or sodium benzoate improved mechanical properties, processability, and productivity in mold processing of the blend [26]. Yokohara et al [4] reported that cellulose nanocrystals improved the barrier properties and increased the Young modulus of the blend.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the traditional fields of synthetic intermediates 1,2 , material chemistry 3,4 , amides play an active role in drug discovery 5 , polymer [6][7][8] , etc and obtained a lot of progress. For example, the importance of the amides in polymer has been recently highlighted by Cai and co-workers 6 .…”
Section: Introductionmentioning
confidence: 99%